FPGA implementation of a single-input fuzzy logic controller for boost converter with the absence of an external analog-to-digital converter - Taeed, Fazel (2012)
In this paper, the single-input fuzzy logic controller (FLC) (SIFLC) for boost converter output-voltage regulation is proposed. The SIFLC utilizes the signed distance method that reduces the multidimensional rule table to 1-D with only one input variable, i.e., distance d. The simplification allows for the control surface to be approximated by a piecewise linear. It is shown that, despite the simplicity of SIFLC, its control performance is almost equivalent to that of the conventional FLC. As a proof of concept, the SIFLC is implemented using the Altera EP2C35F672C6N field-programmable gate array (FPGA) and applied on a 50-W boost converter. The SIFLC is compared to the proportional–integral controller; the simulation and practical results indicate that SIFLC exhibits excellent performance for step load and input reference changes. Another feature of this work is the absence of an external analog-to-digital converter (ADC). Instead, a simple analog-to-digital conversion scheme is implemented using the FPGA itself. Due to the simplicity of the SIFLC algorithm and the absence of an external ADC, the overall implementation requires only 408 logic elements and five input–output pins of the FPGA. Index Terms—Boost converter,